Law Enforcement of Criminal Defamation Through Electronic Media - Putri, Septavela Gusti; Irianto, Echwan; Prihatin AN, Dodik (Lentera Hukum, 2019)
Defamation through Electronic Media as regulated in Article 27 paragraph (3) of Law No. 19 of 2016 on amendments to Law No. 11 of 2008 on Information and Electronic Transactions does not explain in detail the elements of "insulting content and/or defamation;” therefore, the understanding of this term is subjective to the victim. Article 27 also includes the phrase "no rights," suggesting that victims' legal rights in response to defamation are limited. Even so, the Information and Electronic Transactions Law (ITE Law - Undang-Undang Informasi dan Transaksi Elektronik) itself does not provide a detailed explanation of these elements. The results found in this study are an objective criteria to assess whether electronic information or electronic documents which can be qualified as defaming. This study argues that defamation occurs if: (a) information or documents are built based on the clarity of the insulted person's identity; (b) the purpose of words is deemed insulting; (c) defamation is addressed to natural person or legal person (d) the content and context of each case, and (e) the allegations. In addition, a person is said to have the right to commit criminal defamation if carried out in the public interest and by being forced to defend himself. Keywords: Criminal Defamation, Electronic Media, Indonesia